Curriculum Adaptation in English Language Classroom - Alfi Hidayatu Miqawati (Politeknik Negeri Jember, 2022)
The article addressed curriculum adaptation in English language classroom. Since language classroom faced many shifts of setting and paradigm, a well-designed curriculum is needed and it is teachers’ duties for doing so. In making curriculum accessible for students with different culture and language, strategies and techniques should be done. This article discussed useful strategies to support the curriculum design and implementation.